Foreign Experience in Administrative Legal Protection of the Environmental Rights of Citizens and Potential for its Use in Ukraine - KOVALSKA, Vita Volodymyrivna (Journal of Advanced Research in Law and Economics, 2018)
The paper analyzes national legislation in the field of administrative legal protection of the environmental rights of the citizens, as well as examines legal regulation of protecting environmental rights in other states. It also offers suggestions for ways to improve administrative legal protection of environmental rights of Ukrainian citizens.